TEACHING WRITING NARRATIVE TEXTS BY USING THE PICTURES OF POP- UP BOOK AS A MEDIA TO JURIOR HIGH SCHOOL STUDENTS - DESTRI ASIRIKA; REFNALDI REFNALDI (Universitas Negeri Padang, 2017)
In education, English has been a compulsory subject for students to learned. One of the skill that student must be achieved is writing. But, there are some problems that students faced in order to the students find difficulties in writing. In this paper, the writer explains some problems in the students’ writing activity. First, the students do not motivate in developed writing skill. Second, the classroom atmosphere does not support students in writing and find the ideas. Third, the students do not find the inspiration in writing. Because of that, the writer introduces the pictures of “Pop- up book” as a media to help students ability in writing. “Pop – up” have a meaning as appear. So, “Pop – up Book” is a one of media of pictures book with the appear pictures when the book are opened. Pictures through Pop – up Book” can be a stimulus for students in developed writing ability in English. In this paper, the writer choose narrative texts as a text that will be used in teaching writing by using the pictures of “Pop – up book”. The writer also explain about the preparation if the teacher want to design pictures story through “Pop – up Book”, how the teacher use the pictures of “pop – up Book” as a media, and how the students attractive in learning,